2014
DOI: 10.1073/pnas.1411959111
|View full text |Cite
|
Sign up to set email alerts
|

The N- and C-terminal autolytic fragments of CAPN3/p94/calpain-3 restore proteolytic activity by intermolecular complementation

Abstract: CAPN3/p94/calpain-3, a calpain protease family member predominantly expressed in skeletal muscle, possesses unusually rapid and exhaustive autolytic activity. Mutations in the human CAPN3 gene impairing its protease functions cause limb-girdle muscular dystrophy type 2A (LGMD2A); yet, the connection between CAPN3's autolytic activity and the enzyme's function in vivo remain unclear. Here, we demonstrated that CAPN3 protease activity was reconstituted by intermolecular complementation (iMOC) between its two aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…We found that two consecutive alternative exons (exons 15 and 16) in Capn 3 transcripts were almost completely skipped in Rbfox- DKO muscle and are likely direct Rbfox targets (Figure 4C). Auto- lytic cleavage within the IS1 region enables proteolytic Capn3 activity, and cleavage within the IS2 region of Capn3 is required for complete degradation and inactivation of Capn3 (Figure S4C) (Ono et al, 2014). Skipping of exons 15 and 16 in Rbfox-DKO muscle likely produces a Capn3 isoform that lacks the cleavage site within the IS2 region, thereby stabilizing active Capn3 and causing it to accumulate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that two consecutive alternative exons (exons 15 and 16) in Capn 3 transcripts were almost completely skipped in Rbfox- DKO muscle and are likely direct Rbfox targets (Figure 4C). Auto- lytic cleavage within the IS1 region enables proteolytic Capn3 activity, and cleavage within the IS2 region of Capn3 is required for complete degradation and inactivation of Capn3 (Figure S4C) (Ono et al, 2014). Skipping of exons 15 and 16 in Rbfox-DKO muscle likely produces a Capn3 isoform that lacks the cleavage site within the IS2 region, thereby stabilizing active Capn3 and causing it to accumulate.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have used calpastatin as a Capn3 substrate (Ono et al, 2004, 2014). Calpastatin is also an endogenous inhibitor of Capn1 and Capn2; we predicted that reduced calpastatin levels in Rbfox DKO would lead to increased Capn1 and Capn2 activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAPN3 encodes CAPN3, a heterodimer consisting of a large and a small subunit, is a major intracellular protease24, although its function has not been well established. Mutations in this gene25 are associated with lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…3C) and even after scaling-up the expression, the amount of full length ADGB was insufficient for further biophysical characterization. This truncation is most probably a result of proteolysis by intracellular proteases or by auto-cleavage by the N-terminal calpain-like domain, a phenomenon commonly observed among calpains [53][54][55][56]. To further evaluate if ADGB autolytic activity would be the source of this potential auto-cleavage we added three different protease inhibitors to the growth medium; the cysteine protease inhibitor E64, the acid protease inhibitor Pepstatin A and the calpain specific Calpain II inhibitor.…”
Section: Expression Of Ngb Ch-iq-ab and Full Length Adgb In Sf9 Cellsmentioning
confidence: 99%